Terrorism’s Persistence as a Historical Paradox: A Personal Recollection of Developing the Research Problem and its Methodological Resolution - Feyyaz, Muhammad (Journal of Professional Research in Social Sciences, 2025)
This research note recollects the beginning of the author’s interest in understanding the paradoxical phenomenon of persistent terrorism, intriguing because of its continued existence, though historically rarely achieving the central goals of its practitioners. It describes how empirical observations of enduring terrorism in Pakistan and around the world ultimately led to its investigation as part of a larger methodologically driven systematic study, culminating in a PhD and later in a book. The research note aims to inspire readers to engage with the topic as a potential contribution toward addressing the terrorism problem. Further, it implicitly highlights a methodological process for the developing scholars and potential researchers studying political violence.